The Principle of Deliberation as a Key Basis of Statehood in Modern Russia - Baranova, Marina; Kuptsova, Olga; Kalandarishvili, Zurab (Տիգրան Մեծ)
The development of statehood is predetermined by a great variety of factors. In modern society, citizens are developing an increasing willingness to fully participate in political and legal processes jointly with the state. Today the ideas of deliberative democracy attract the close attention of legal theorists in this aspect. The subject of the research is the key aspects of the philosophical and legal treatment of social relations in the sphere of realisation of the principle of deliberation in modern Russia. The purpose of this study is a multilevel analysis (general legal, philosophical, technical/legal) of the principle of deliberation, with substantiation of its significance as a key foundation of statehood in modern Russia. The research results confirm the initial hypothesis and evidence that the goal of the study has been achieved. The correlation of state and public interests in terms of deliberative interaction is of fundamental importance for the development of Russian statehood.
Keywords: Self-regulation; Philosophy of Law